2019
DOI: 10.1108/jrit-01-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

Social and emotional learning for parents through Conscious Discipline

Abstract: Purpose The purpose of this paper is to examine Conscious Discipline’s (CD) Parenting Education Curriculum (CD PEC), the parenting component of CD’s research-based social and emotional learning program. CD aims to change child behavior by changing how adults understand and manage their own behaviors and emotions. Researchers explored CD PEC’s association with improved parenting skills, parent–child relationships and child behavior and emotion management. Design/methodology/approach During pre- and post-site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…e teaching method presents the development trend of three-dimensional, multi-channel, long-distance, real-time, interactive transmission, which greatly expands the transmission method and space of teaching information, especially with the emergence of multimedia technology, network technology, and virtual technology, the roles of modern and traditional teaching media in education are not mutually exclusive. e combined use of the two is conducive to the dissemination of teaching materials, the smooth promotion of teaching reform, and the expansion of teaching influence [9]. Emotion recognition is the intelligent recognition of human emotions.…”
Section: Intelligent Teaching Mode Based On Emotion Recognitionmentioning
confidence: 99%
“…e teaching method presents the development trend of three-dimensional, multi-channel, long-distance, real-time, interactive transmission, which greatly expands the transmission method and space of teaching information, especially with the emergence of multimedia technology, network technology, and virtual technology, the roles of modern and traditional teaching media in education are not mutually exclusive. e combined use of the two is conducive to the dissemination of teaching materials, the smooth promotion of teaching reform, and the expansion of teaching influence [9]. Emotion recognition is the intelligent recognition of human emotions.…”
Section: Intelligent Teaching Mode Based On Emotion Recognitionmentioning
confidence: 99%
“…Fourteen studies centred on promoting the development of pro‐social behaviours among students were analysed. These studies have shown interventions with diverse modes of delivery, including formal programmes (Chong et al, 2013; Flower et al, 2014; Smith‐Carrier et al, 2015; Torok et al, 2019; Yeung et al, 2016), parenting‐focused programmes (Darling et al, 2019), mentor assistance programmes (Glazzard et al, 2021), sports activities (Spaaij, 2012), and through animal protection programmes (Baatz et al, 2020; Hawkins et al, 2019; Jamieson et al, 2012; Lakestani et al, 2015; Mariti et al, 2011; Williams et al, 2022), both within and outside school.…”
Section: Methodsmentioning
confidence: 99%
“…According to NASEM ( 2016), the more parents understand children's developmental patterns and utilise quality nurturing techniques, the better positioned they are to promote their children's interpersonal interactions. Moreover, Darling et al (2019) conducted a study to investigate the impact of parenting education with a specific emphasis on conscious discipline in SEL programmes. In this study, parents participated in pre-and post-data collection and were provided with an intervention.…”
Section: Pro-social Behaviour Developmentmentioning
confidence: 99%
“…The SBG pilot study was a parallel single-blind, waitlist-controlled, post-only design, enrolling children and their parents who were either participating or wait-listed in a community-based intervention (St. George’s University IRB #14099; https://clinicaltrials.gov/ct2/show/NCT04697134 ). The intervention was based on the Conscious Discipline curriculum ( 46 , 49 ), which aims to build adult caregivers’ skills in non-violent child discipline. For implementation, SBG partnered with the Roving Caregiver Program, a home visiting service providing infant stimulation to at-risk Grenadian children ages 0–3 ( 50 ).…”
Section: Methodsmentioning
confidence: 99%